The Effectiveness of Brief Information and Self-Efficacy-Based Interventions in Influencing Snack Choices in Homeless Individuals - Emmerson, Chris; John, Bev; Faulkner, Susan; Lancastle, Deborah; Roderique-Davies, Gareth (Frontiers in Public Health, 2017)
Background: Homeless adults frequently experience poor nutrition. Research suggests raising self-efficacy and nutritional knowledge can increase healthy eating but that the choice of specific behavioural change techniques is also critical. This study investigated how behavioural change techniques, operationalised to increase nutrition knowledge and self-efficacy might influence the choice of homeless adults when presented with a ‘healthy’ and an ‘unhealthy’ snack. Method: A total of 125 homeless adults were randomly allocated to watch one of four brief films: ‘control’, ‘[nutrition] information only’, ‘self-efficacy’ (aimed at increasing self efficacy and general healthy eating knowledge) and ‘enhanced self efficacy’ (as ‘self efficacy’, but the presenter identified themselves as a homeless adult). Post-film, participants were invited to choose between a healthy and an unhealthy snack. Results: Data were analysed using ANOVA and chi square. Participants in the ‘enhanced self efficacy’ condition were significantly more likely to choose the healthy option compared to those in the control condition; for the ‘self-efficacy’ condition the difference was marginally significant. Perceived knowledge and self-efficacy were significantly associated and those with high self-efficacy were significantly more likely to choose a healthy snack regardless of condition. Conclusion: Homeless adults are more likely to make healthy snack choices if their nutritional self-efficacy is increased through encouragement by a peer.